2016
DOI: 10.3386/w22601
|View full text |Cite
|
Sign up to set email alerts
|

Migration as a Test of the Happiness Set Point Hypothesis: Evidence from Immigration to Canada

Abstract: for comments on earlier versions. Responsibility for opinions and errors remains with the authors. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…For our study, we assume that measures of median income and regional unemployment can have both positive and negative implications for happiness, but we are interested in the overall trend of the combined CBSAs as related to regional happiness. Prior studies also indicate aggregate measures of age [9,46,53], education levels [54], immigration levels [55], and access to healthcare [56] to be determinants of individual happiness. Similarly, regional disability rates have been found to correlate with levels of happiness, particularly when the disability is most likely to affect work outcome [32].…”
Section: Methodsmentioning
confidence: 99%
“…For our study, we assume that measures of median income and regional unemployment can have both positive and negative implications for happiness, but we are interested in the overall trend of the combined CBSAs as related to regional happiness. Prior studies also indicate aggregate measures of age [9,46,53], education levels [54], immigration levels [55], and access to healthcare [56] to be determinants of individual happiness. Similarly, regional disability rates have been found to correlate with levels of happiness, particularly when the disability is most likely to affect work outcome [32].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, migration is usually directed towards countries of higher prosperity and wealth. Recent studies have shown that emigrants are happier and report higher well-being after migration compared to their home populations (Fanninh, Haase, & O'Boyle, 2011;Frank et al, 2016;Helliwell, Bonikowska, & Shiplett, 2016a;Measuring and Reporting on Europeans' Wellbeing, 2015;Melzer, 2011;Nowok, Van Ham, Findlay, & Gayle, 2013;Stillman, Gibson, McKenzie, & Rohorua, 2015;Tabor & Milfont, 2011). This is especially valid for work migrants (Switek, 2016) and those who migrated from low or middle "happy" countries (Helliwell et al, 2016a).…”
Section: Introductionmentioning
confidence: 98%
“…Recent studies have shown that emigrants are happier and report higher well-being after migration compared to their home populations (Fanninh, Haase, & O'Boyle, 2011;Frank et al, 2016;Helliwell, Bonikowska, & Shiplett, 2016a;Measuring and Reporting on Europeans' Wellbeing, 2015;Melzer, 2011;Nowok, Van Ham, Findlay, & Gayle, 2013;Stillman, Gibson, McKenzie, & Rohorua, 2015;Tabor & Milfont, 2011). This is especially valid for work migrants (Switek, 2016) and those who migrated from low or middle "happy" countries (Helliwell et al, 2016a). Meanwhile, the analysis of satisfaction with life scores between immigrants and host country populations revealed no differences (Frank et al, 2016;Helliwell et al, 2016a;Senik, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations